EGFR and coronary artery calcification in chronic kidney disease. (28th March 2019) - Hyun, Young Youl; Kim, Hyang; Oh, Kook‐Hwan; Ahn, Curie; Park, Sue K.; Chae, Dong Wan; Oh, Yun Kyu; Choi, Kyu Hun; Han, Seung Hyeok; Kim, Yeong Hoon; Lee, Kyu‐Beck
Abstract: Background: The independent association between eGFR and coronary artery calcification (CAC) is complex and not clear. The aim of this study was to investigate the relationship between eGFR calculated from different equations and CAC in predialysis CKD patients in Korea. Methods: In this cross‐sectional study, we analysed 1533 patients from the KNOW‐CKD cohort. eGFR was calculated by a four‐variable MDRD equation (eGFRMDRD ), CKD‐EPI creatinine equations (eGFRCr ), CKD‐EPI cystatin C equation (eGFRCys ) and CKD‐EPI creatinine‐cystatin equation (eGFRCrCys ). Participants were divided into eGFR categories (<30, 30‐59, 60‐89, ≥90 mL/min/1.73 m 2 ). CACS (coronary artery calcium score) was measured using cardiac computed tomography. CAC was defined as CACS >100. Results: Coronary artery calcification was found in 334 (21.8%) patients and was more prevalent in the lower eGFR groups ( P < 0.001). In multivariate Tobit regression, CACS increased gradually as eGFRCrCys decreased ( P for trend = 0.034). In multivariate logistic regression, there were gradual associations between lower eGFR and CAC when an eGFRCys or eGFRCrCys was used. The adjusted OR for CAC in the group with eGFR <30 mL/min/1.73 m 2 compared to the group with eGFR ≥90 mL/min/1.73 m 2 was 2.64 (95% CI, 1.09‐3.60) when eGFRCrCys was used. Of the four eGFR formulas, only adding eGFRCrCys significantly improved CAC prediction models without eGFR ( P = 0.046). Conclusions: There was a gradual and independent association between low eGFR and CAC in a predialysis CKD cohort in Korea. eGFRCrCys predicted CAC better than other equations in this population.